2008
DOI: 10.1002/ajp.20541
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age on fecal steroid hormone levels in male Budongo Forest chimpanzees (Pan troglodytes schweinfurthii)

Abstract: Potential interactions between age and endocrinological functioning have been understudied in wild ape populations. Therefore, we examined the relationship between age and the secretion of androgens and glucocorticoids in 15 juvenile, subadult, and adult male chimpanzees (Pan troglodytes schweinfurthii) free ranging in the Budongo Forest of Uganda. One hundred and nine fecal samples were opportunistically collected, between 07:30 and 13:30 hr, during the wet season. Fecal samples were preserved, by oven drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 47 publications
1
29
0
1
Order By: Relevance
“…An increase of GC concentrations with age is also known from humans (e.g. [10,31]) and chimpanzees [58]. Among the many possible mechanisms explaining GC elevation in older humans is reduced Fig.…”
Section: Discussionmentioning
confidence: 97%
“…An increase of GC concentrations with age is also known from humans (e.g. [10,31]) and chimpanzees [58]. Among the many possible mechanisms explaining GC elevation in older humans is reduced Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Tanner & Gupta 1968, Kelnar & Brook 1983, Remer et al 1994. One study on DHEA-S levels in chimpanzee feces did not detect the age-related changes that were found in serum samples (Seraphin et al 2008), but it should be noted that individuals of age categories that are most likely to show the sudden upward shift in DHEA-S were under-represented. There are other preliminary reports on DHEA-S levels in chimpanzees that have used fecal or urine samples (Fontenote et al 2001, Anestis et al 2009), but between-species comparisons are still difficult.…”
Section: Discussionmentioning
confidence: 97%
“…However, studies reporting individual hormone levels (rather than age-specific groups) found no discernible increase in DHEA or DHEAS during the peripubertal period (Nadler et al 1987, Bernstein et al 2012. Furthermore, fecal concentrations of DHEAS were actually higher in juveniles (5-9 years of age) than in either subadults (10-15 years) or adults (16C years) (Seraphin et al 2008). The earliest studies on circulating adrenal androgen concentrations in gorillas had a limited number of subjects, none of which were prepubertal age (Cutler et al 1978).…”
Section: Endocrinological Adrenarchementioning
confidence: 93%